A higher quality of life by the Cervantes Short-Form Scale is related to a better sexual desire in postmenopausal women. (2nd November 2021) - Fasero, Maria; Jurado-López, Ana Rosa; San Martín-Blanco, Carlos; Varillas-Delgado, David; Coronado, Pluvio J.
Abstract: Objective: Evaluate the association between health relate quality of life and sexual desire in postmenopausal women and the influence of demographic descriptors on sexual desire. Methods: A observational-cross-sectional study was conducted in 521 postmenopausal women in La Zarzuela Hospital between 2018-2020. Cervantes-short form (Cervantes-SF) scale and Brief profile female sexual function (B-PFSF) scale were filled out in the consultation. High score in Cervantes-SF implies worse health-related quality of life (HR-QoL). If score is lower or equal to 20 in B-PFSF implies diagnosis of hypoactive sexual desire disorder. Results: There is a positive relationship between HR-QoL measured by Cervantes-SF and sexual desire measured by B-PFSF ( p < .001; correlation coefficient: .223). The mean score on Cervantes-SF was 30.8 ± 14.9 and on B-PFSF was 18.7 ± 7.4. The B-PFSF score was worse in those women using systemic or vaginal hormonal treatment versus using non-hormonal treatment (18.7 ± 7.8 or 17.2 ± 7.4 vs 19.7 ± 6.5; p = .033. Smoking (b exp: .384; p = .029) and using vaginal hormonal treatment (b exp: 1.759; p = .033) are independent factors related to sexual desire. No difference was found in the wellbeing perceived by women in the different treatments (mean of minimal clinically important difference score was 2.9 in systemic vs. 3.0 in vaginal hormonal treatment). Conclusions: Improvement on HR-QoL is related to improvement on sexual desire. Sexual desire is better in women with non-hormonal treatment than in women with systemic or vaginal hormonal treatment. The vaginal hormonal treatment and being current smoker are independent factors of low and high sexual desire, respectively.